ETS-10 zeolite – A potential material for catalyst and adsorption: A critical review - Bich-Ngoc Duong; Thi-Phuong-Tu Nguyen; Duy-Khoi Nguyen; Thuy-Hang Nguyen; Ngoc Duy Nguyen; Van-Phuc Dinh (Desalination and Water Treatment)
Zeolite Engelhard Titanosilicate – 10 (ETS-10) is an advanced material synthesized from titanium (Ti) and silica (Si) sources, emerging as a promising candidate for numerous applications in recent years. This review explores recent advances in the synthesizing of ETS-10 zeolite from various cost-effective and environmentally friendly precursors, such as P25, TiO₂ anatase, fly ash, and rice husk ash. These developments have paved the way for large-scale ETS-10 synthesis. The use of natural chemical sources can produce ETS-10 with a structure similar to that synthesized from pure chemical sources. However, its morphology, pore size, and surface area are entirely dependent on the precursor source, as well as key synthesis factors such as component ratios, pH, and template selection. Therefore, optimizing synthesis conditions and exploring new templates to achieve the desired material properties are key research directions that scientists are actively investigating. Finally, this study highlights the remarkable potential of ETS-10 in catalysis and adsorption applications, as demonstrated by previous research, advocating its use as an environmentally friendly solution for effective environmental treatment.